Sudden Hearing Loss and Autoimmune Inner Ear Disease - Campbell, Kathleen C. M.; Klemens, James J. (Journal of the American Academy of Audiology, 2000)
This case report describes the audiologic and medical diagnostic evaluations, results, and treatment options in a patient with a classic presentation of immune-mediated sensorineural hearing loss, commonly called autoimmune inner ear disease (AIED). It reviews findings of the basic battery, immittance audiometry, transient otoacoustic emissions, and auditory brainstem response measures and medical findings over more than 2 years. AIED generally causes asymmetric bilateral sensorineural hearing loss with atypical configuration. Although hearing loss is generally fluctuant, the overall pattern is usually rapid progression, particularly in the absence of early medical intervention. Word recognition is usually disproportionately poor. In our case, otoacoustic emissions and auditory brainstem responses suggest both cochlear and retrocochlear involvement and may initially appear to be inconsistent with pure-tone thresholds. Audiologists must be familiar with AIED because early identification is critical. Additionally, an immunologic basis may be a factor in other disorders, including many cases of Meniere's disease.Abbreviations: AIED = autoimmune inner ear disease, FTA/ABS = fluorescent treponemal antibody/absorption, MLR = middle latency response, MRI = magnetic resonance imaging, TOAEs = transient otoacoustic emissions
Keywords: Auditory evoked potentials; autoimmune inner ear disease; otoacoustic emissions; sensorineural hearing loss; sudden hearing loss